Improved Perceptions of Education and Wellness Among General Surgery Residents and Faculty After the Implementation of Outpatient Scribes. Issue 10 (October 2021) - Tohmasi, Steven; Naaseh, Ariana; Thompson, Sean; Smith, Brian R.
Background: Recent studies have revealed a high rate of burnout among general surgery (GS) residents. Efforts to design and implement interventions to mitigate fatigue in surgical trainees are critical. Our aim was to assess the educational and wellness impact of outpatient scribe utilization at an academic GS residency program. Methods: Electronic surveys were sent to 38 GS residents and 15 faculties who used outpatient scribes for at least 12 months. Questions were scored on a 5-point Likert scale with answers of "Strongly agree" or "Agree" representing affirmative responses. Results: Thirty residents and 14 faculty completed the survey, resulting in an 83% overall response rate. Twenty-eight (93%) residents and 12 (86%) faculty believed that scribes decrease the daily workload of trainees. Twenty-seven (90%) residents felt that scribes allow them more time to focus on patient care and improve the quality of their surgical education. Ninety-three percent of residents (n = 28) and faculty (n = 13) believed that scribes enhance resident well-being. Twenty-four (80%) residents reported that scribes help improve adherence to duty hour restrictions. Twenty-five (83%) residents believed that utilizing scribes is an effective fatigue mitigation strategy for surgical training programs. Conclusion: Our findings demonstrate that the implementation of an outpatient scribe program at an academic GS residency program may enhance resident education and wellness.